Studies on Albumin Polymorphism in Bangladeshi Cattle (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Biochemical polymorphism; albumin; native cattleBangladesh j. genet. biotechnol. 5 (1&2): 53-56, 2004 (June & December)